4CPS-178 Transcription of supportive medication for inpatient chemotherapy by designated oncology ward pharmacists. (24th March 2020) - Imaz, C; Smith, E; Fox, A; Wright, D; Carson, L
Abstract : Background and importance: Following several incidents where patients' supportive treatments were omitted, a safety measure in the verification process for inpatient chemotherapy (IPChx) treatment was implemented. Oncology ward pharmacists (OWPs) must ensure supportive medications are transcribed from ARIA (chemotherapy prescribing software) to JAC (inpatient prescribing software) before chemotherapy is released to the ward. Current practice is for clinicians to complete the transcribing, and delays in prescribing these may delay chemotherapy administration. This can impact on the pharmacy service, hospital workflow, and patient care and satisfaction. Aim and objectives: To evaluate whether the transcribing pharmacist role reduces IPChx delivery time and occurrence of transcribing errors. Material and methods: Stage 1 (control): the clinician led process of transcribing was mapped and the time taken for each stage recorded by OWPs for 4 weeks (February–March 2019) using a piloted data collection form. Stage 2 (active period): OWPs carried out the transcription. Transcription and delivery to patient times were again recorded using the same data collection form (June–July 2019). Stages 1 and 2 mean delivery to patient and transcribing process times were compared using a Student's t test and Welch t test, respectively. Transcribing error rates for each stage were compared using a χ 2 test. Results: The mean IPChx delivery time during the active period was 50.2 hours (range 24.7 to 75.7), a decrease of 23.7 hours (95% CI −15.4 to 62.8) compared with the control period (p=0.228). There was a notable decrease in screening process time, from 7.8 hours (range 4 to 11.6) in the control to 3.5 hours (range 1.8 to 5.2) in the active period, a statistically significant difference of 4.3 hours (95% CI 0.2 to 8.5, p=0.039). The transcribing error rate during the active period was 4%, lower than the 27% in the control period (χ 2 (1)=36.46, p<0.001). Conclusion and relevance: Involving OWPs in transcribing supportive medication reduced the IPChx delivery time and the occurrence of transcribing errors. Nonetheless, inconsistencies between current practice and hospital targets raised important issues that may imply that a further evaluation of the whole IPChx process is required. Consequently, further research is required to establish if additional interventions are required to improve waiting times for oncology patients. References and/or acknowledgements: Conflict of interest: Corporate sponsored research or other substantive relationships: This project was completed as part of the MSc Advanced Clinical Pharmacy Practice programme at Queen's University Belfast. This was funded with the Pharmacy Fund Award granted by the Southampton Pharmacy Research Centre at University Hospital Southampton NHS Foundation Trust.